2013
DOI: 10.1016/j.palaeo.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of climate change for the last 20,000years from Wonderkrater, South Africa: Implications for the long-term dynamics of the Intertropical Convergence Zone

Abstract: Highlights Quantitative estimates of climate at a key South African site over the past 20 kyr. Reconstructed trends show strong links with regional sea-surface temperatures. Reconstructions indicate interhemispheric synchrony in the African tropics. Findings do not support the hypothesis of direct insolation forcing of tropical African climates. Highlights a promising technique for analyzing palaeobotanical data in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
107
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 54 publications
(80 reference statements)
9
107
0
1
Order By: Relevance
“…Many different strategies have been proposed (Kühl et al, 2002;Gebhardt et al, 2007;Truc et al, 2013), all of them fitting a PDF to the pollen types identified in the fossil record. This strategy leads to a loss of certain information because (1) individual signals are mixed and (2) rare species are masked by the most extended ones.…”
Section: Fitting Of the Pdfsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many different strategies have been proposed (Kühl et al, 2002;Gebhardt et al, 2007;Truc et al, 2013), all of them fitting a PDF to the pollen types identified in the fossil record. This strategy leads to a loss of certain information because (1) individual signals are mixed and (2) rare species are masked by the most extended ones.…”
Section: Fitting Of the Pdfsmentioning
confidence: 99%
“…They rely on the fundamental hypothesis that a causal relationship exists between the modern distributions of plants and the associated climates (Jackson and Williams, 2004, and references therein). These techniques can be divided into two types: (1) those based on plant assemblages -modern analogue technique (MAT) (Overpeck, 1985;Guiot, 1990), weighted averaging (WA) (ter Braak and Looman, 1986;ter Braak and van Dame, 1989;Birks et al, 1990), weighted averaging-partial least-squares regressions (WA-PLS) (ter Braak and Juggins, 1993), artificial neural networks (ANNs) (Malmgren et al, 2001) or regression trees (Salonen et al, 2012) -and (2) those based on plant distributions -mutual climatic range (MCR) (Atkinson et al, 1987;Sinka and Atkinson, 1999;Elias, 1997), the coexistence approach (CA) (Mosbrugger and Utescher, 1997;Utescher et al, 2014) or probability density functions (PDFs) (Kühl et al, 2002;Truc et al, 2013). These methods are fully detailed in Birks et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations